2017
DOI: 10.1039/c7ra01065f
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of PEBA/Cu2O mixed-matrix membranes and their application in pyridine recovery from aqueous solution

Abstract: The lone pair of electrons of the pyridine nitrogen atom can form a complex with some metal ions such

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…FT-IR spectra of MoS 2 , PEBA/MoS 2 -0, and PEBA/MoS 2 -10 are shown in Figure . The bands around 3500–3300 and 1646 cm –1 are attributed to the N–H stretching vibration of polyamide and the stretching vibration of the H–N–CO group, respectively, as shown by PEBA/MoS 2 -0. It is noteworthy that an obvious band at 3436 cm –1 attributed to the O–H stretching, was observed for MoS 2 and the PEBA/MoS 2 -10 membrane.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…FT-IR spectra of MoS 2 , PEBA/MoS 2 -0, and PEBA/MoS 2 -10 are shown in Figure . The bands around 3500–3300 and 1646 cm –1 are attributed to the N–H stretching vibration of polyamide and the stretching vibration of the H–N–CO group, respectively, as shown by PEBA/MoS 2 -0. It is noteworthy that an obvious band at 3436 cm –1 attributed to the O–H stretching, was observed for MoS 2 and the PEBA/MoS 2 -10 membrane.…”
Section: Resultsmentioning
confidence: 92%
“…Table describes the comparison of the pervaporation performance of the PEBA/MoS 2 hybrid membrane with other membranes reported in the literature. ,,, It can be found that the PEBA/MoS 2 hybrid membrane exhibits encouraging pervaporation performance.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, it is important to recover pyridine from wastewater, which is both beneficial to the environment and economic value. A significant number of studies have been conducted on pyridine wastewater treatment, such as adsorption and extractive distillation. ,, However, it is difficult to recycle pyridine from a dilute aqueous solution . On the one hand, pyridine and water would form an azeotrope at 93.6 °C, with 59 wt % pyridine in it; on the other hand, pyridine is present in effluents at a low concentration, which makes the recovery of pyridine a huge challenge. As a green membrane separation technique for separating azeotropic liquid mixtures, pervaporation could reduce 50–70% energy consumption in many cases as compared to the traditional separation processes, and as a result, it has received extensive attention from researchers. …”
Section: Introductionmentioning
confidence: 99%
“…Pervaporation has numerous advantages over other conventional techniques: high separation efficiency, efficiency in breaking azeotropes [13] and microemulsions [14][15][16]; being non-polluting, energy saving, easy to incorporate in production lines, used in industrial refining processes; and environment protection (water treatment). This process is mainly used for dehydrating organic and hydro-organic compounds [16][17][18], removing organic matter at low concentrations from aqueous solutions [19][20][21], and separating organic-organic compounds [22][23][24].…”
Section: Introductionmentioning
confidence: 99%